1998
DOI: 10.1111/1468-0092.00060
|View full text |Cite
|
Sign up to set email alerts
|

Islets through Time: The Definition, Dating and Distribution of Scottish Crannogs

Abstract: Scottish crannogs or lake dwellings are considered to be structurally varied sites with an extremely wide distribution, used from the neolithic up until at least the 17th century AD. As a result assumptions about the dating and form of individual sites are considered impossible without excavation. This paper demonstrates that the current classifications lack utility and that the long chronology view is misleading. It is suggested that there is a far more subtle spectrum of identifiably distinct monuments which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 3 publications
1
27
0
Order By: Relevance
“…More recently, several studies have added to the discussion (Barber and Crone 1993;Henderson 1998;Dixon 2004). …”
Section: Discussionmentioning
confidence: 99%
“…More recently, several studies have added to the discussion (Barber and Crone 1993;Henderson 1998;Dixon 2004). …”
Section: Discussionmentioning
confidence: 99%
“…Over 500 of these artificial islands are known (Lenfert, 2012), and are frequently encountered as small islands or submerged mounds in lochs. In Scotland, the known distribution of crannogs, which sees high densities of sites in western regions and very few sites in eastern areas, has been viewed as significant and linked to wider interpretations of crannogs' date and function (Munro, 1882: 248-9;Henderson, 1998Henderson, : 240-2, 2009Cavers, 2010: 26-36;Lenfert, 2013). The understood distribution has informed research strategies which have regularly targeted regions with a wellestablished crannog resource (e.g.…”
Section: Drainage and Impacts To The Archaeological Recordmentioning
confidence: 99%
“…While this work has greatly increased our understanding of the site-type in the region, the degree to which these datasets are applicable to other regions is unclear, and making wider interpretations of the artificial island dwelling phenomenon in Scotland problematic. Most notably, the assertion that crannogs were predominately a phenomenon of western Scotland in later prehistory has been made (Henderson, 1998(Henderson, , 2009Cavers, 2006Cavers, , 2010Henderson, 2009;Lenfert, 2013). If crannogs are recognised as being a building tradition constructed nearly ubiquitously wherever suitable loch conditions existed in Scotland in the first millennium BC, then interpretations based on a western distribution of crannogs must be reassessed.…”
Section: Re-constructing Lost Lochs and Implications For The Archaeolmentioning
confidence: 99%
“…Since the discovery of Eilean Domhnuill on North Uist it has been considered a possibility that lake settlement forms in Scotland have been in existence since the Neolithic (Armit 1996), while in Ireland the existence of related lake ‘platform’ structures dating to the Mesolithic has been established (O'Sullivan 1998; Fredengren 2002). However, closer analysis of the dating evidence for crannogs has indicated that the majority of sites belong to the ‘Later Prehistoric’ period, broadly taken to be the period 1000 BC to AD 500 (Crone 1993; Henderson 1998). The aim of this paper is to identify the evidence for the origins of lake settlement forms in Scotland and Ireland, considering the likely origin of the concept of the ‘crannog’, as well as the physical evidence for the structure of early lake settlements and their relationship to contemporary terrestrial settlements.…”
Section: Introductionmentioning
confidence: 99%